2019
DOI: 10.1002/pc.25338
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of biocomposites based on sponge‐gourd natural fiber reinforced poly(lactic acid)

Abstract: To prepare fully biodegradable materials, variable concentrations of luffa fiber (LF) namely 1, 3, and 5 phr, were incorporated into a poly(lactic acid) (PLA) matrix. To counteract the poor adhesion of the LF to PLA, a compatibilizer which is maleic anhydride‐grafted poly(lactic acid) has been incorporated and the properties of the composites with and without compatibilizer noted, respectively, PLA/LF and PLA/PLA‐g‐maleic anhydride (MA)/LF, were compared. The final torque of PLA/LF was found to decrease with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…This is due to the agglomeration, orientation, micro-gaps between PLA and the fibers, and exposed surfaces of the fibers that were not entirely covered by the polymeric matrix, 41 which easier water transport through the material. 40,42 Besides, both agave and coir fibers showed similar behaviors.…”
Section: Water Absorption and Weight Loss By Hydrolytic Degradationmentioning
confidence: 92%
See 1 more Smart Citation
“…This is due to the agglomeration, orientation, micro-gaps between PLA and the fibers, and exposed surfaces of the fibers that were not entirely covered by the polymeric matrix, 41 which easier water transport through the material. 40,42 Besides, both agave and coir fibers showed similar behaviors.…”
Section: Water Absorption and Weight Loss By Hydrolytic Degradationmentioning
confidence: 92%
“…Water absorption values of PLA (less than 3%) showed a tendency of the terminal polar groups of PLA molecules to the hydrophilicity. 40 For biocomposites, it was observed that as the amount of fiber increases, so does the amount of absorbed water. This is due to the agglomeration, orientation, micro-gaps between PLA and the fibers, and exposed surfaces of the fibers that were not entirely covered by the polymeric matrix, 41 which easier water transport through the material.…”
Section: Water Absorption and Weight Loss By Hydrolytic Degradationmentioning
confidence: 99%
“…41 In the spectra of the coupled composites, a small change in the region related to the presence of the C ¼ O group (�1730 cm �1 ) can also be observed, with a slight increase in peak intensity in these composites in relation to the rPP-MB-30 sample, due to presence of CA, which has a carbonyl group in its structure. 30 Rahen et al 42 also observed an increase in the interfacial reaction between the maleic anhydride groups of the compatibilizer and the hydroxyls of the fiber. This result was evidenced from the Fourier transform infrared spectroscopy that pointed out the disappearance of the vibration band due to the anhydride groups of the compatibilizer of the spectra of the composite and the best impregnation of the fiber by the matrix as observed in scanning electron microscopy.…”
Section: Selecting the Best Coupling Agent Ratiomentioning
confidence: 93%
“…Pickering, Efendy and Le 5 also observed that MAgPP improved strength and tensile and flexural strength as well as impact strength in PP matrix composites. Rahen et al 42 study where varying concentrations of luffa fiber was incorporated into a poly (lactic acid) matrix and, to neutralize the poor adhesion of the fiber to the matrix, the maleic anhydride compatibilizer was used showed that the impact strength of the compatibilized composites was seen to increase, especially whereas the water uptake aptitude was considerably reduced.…”
Section: Selecting the Best Coupling Agent Ratiomentioning
confidence: 99%
“…Many cellulosic derivatives were introduced into PLA matrices in the presence of PLA-g-MA to improve the mechanical properties of blends such as Luffa [26], flax [27], coffee grounds [28], wood flour or rice husk [29,30], sisal fibers [31], straw [32], bamboo fiber [33], cassava starch [34,35], starch [36], and lemongrass fiber [37]. For example, the use of PLA-g-MA in a PLA/cassava starch blend has a significant impact on elongation at break but not on Young's modulus or tensile strength.…”
Section: Pla-g-cellulosic Derivativesmentioning
confidence: 99%